Web Portal For Health Disclosure: A Promising Future. - Zakaria, Nasriah (2007)
This poster presents the idea of developing web portal for health disclosure in the future. Some preliminary data on disclosure behaviors by patients give some promising hope for the use of Information and Communication Technologies (ICT) specifically for health disclosure in the coming future. A concept of web portal is also introduced in this poster.